Substitution of natural feed with artificial feed on the survival rate and growth rate of giant-snakehead Channa micropeltes - Sarmila; Susilawati Susilawati; Sri Warastuti (Jurnal Akuakultur Indonesia)
The purpose of this study was to determine the best percentage of artificial feed substitution for growth and survival rate of giant-snakehead. This study used a completely randomized design (CRD) with 4 levels of artificial feed substitution dose treatment, namely 25%, 50%, 75%, 100%, and control (without artificial substitution). The feed used in the form of fresh trash fish mixed with artificial feed FF-999 with a protein content of 35%. The results showed that the control treatment (100% trash fish) gave the best survival rate and spesific growth rate of 75% and 2.12%/day, respectively. Meanwhile, the percentage of artificial feed substitution treatment which gave the best survival rate and specific growth rate was found in the substitution percentage treatment of 25% artificial feed with a survival rate of 66.67% and a daily weight growth rate of 1.89%/day. Substitution of 100% artificial feed caused death with a 0% survival rate.